Implementation Model on Accommodative Higher Education for Persons with Disabilities at State Islamic University of Alaudin Makassar - Soleh, Akhmad (Indonesian Academy of Social and Religious Research (IASRR), 2023)
The interest in studying among students with disabilities is very high, but the availability of PTKIN, which has provided aspects of higher education for persons with disabilities, is still limited. This study aims to examine the implementation model of accommodative higher education for persons with disabilities at UIN Alaudin Makassar. This research is qualitative field research where the data collection technique uses survey, interview, and documentation methods. The data analysis technique uses an interactive model developed by Miles and Huberman. The primary data sources are the Rector, vice-rectors, lecturers, academics, and students with disabilities. The results showed that the views and understanding of leaders and lecturers at UIN Alauddin Makassar are still traditional, although there is also a tendency to have social nuances. The learning system at UIN Alauddin Makassar is still nuanced; integration has yet to organize inclusive education. The environment and campus buildings are not fully accessible to persons with disabilities.